ANALYSIS OF THE EFFICIENCY OF THE MANAGEMENT OF PRIVATE HIGH SCHOOLS (JURNAL ECONOMICA : Research of Economic And Economic Education, 2021)
This study aims to analyze factors or inputs that affect the number of graduates of private high schools in Jambi City and measure the level of technical efficiency of private high schools in Jambi City. The results showed that the factors or inputs that influenced the number of private high school graduates in Jambi city from 2015-2019 were students and classrooms. While the factors or inputs that do not affect the number of graduates are study groups, teachers, administrative personnel and support rooms. The technical efficiency level of 27 private high schools in Jambi city from 2015-2019, the highest in 2015 reached 0,78 = 78%, the lowest figure occurred in 2019 only 0,27 = 27% and the average only reached0,49 = 49%, this explains that the efficiency of managing private high schools in Jambi city has not been efficient. The results of the study recommended that private high schools in Jambi city be technically efficient by optimizing the achievement of graduate competencies consisting of qualification criteria of learners' abilities that are expected to be achieved after completing their studies in the secondary education unit and the addition of classrooms is necessary to create a comfortable and disciplined learning atmosphere, orderly, anti-smoking and drugs, harmony between teachers, students and parents and maintain optimal conditions in the learning process.